Specific Expertise Use While Investigating Illegal Arms Trafficking - Elchyn ohly Veliiev, Rustam (Archives of Criminology and Forensic Sciences, 2024)
Investigation of criminal offenses related to illegal circulation of weapons is impossible without the use of special knowledge, at least without knowledge in the field of forensic ballistics in particular and forensic weapons science in general. In view of prevalence in the specific weight of the recorded criminality of the specified criminal offenses, article purpose is defined as the clarification of typical forms of specific expertise use implemented at the stage of pre-trial investigation of criminal offenses related to the illegal circulation of weapons, establishment of problematic issues that arise in law enforcement activities on this matter. On the basis of conducted analysis, it was established that specific expertise use in the field of forensic weapons science is typical that most often consists in implementation of three forms, in particular, during investigative (search) actions, in the form of a forensic examination, during preliminary forensic investigations. It is substantiated that only two of the specified forms contribute to obtaining procedural sources of evidence, while preliminary research and checks on forensic records, in turn are aimed at obtaining orientation information.